Caught between autocracy and jihadism: Syria's Christians hope for the implementation of Geneva I - Becker, Petra (SWP Comments, 2014)
The discourse conducted by Syria's Christians since March 2011 reveals that many of them have now turned their back on the protest movement, despite their initial sympathy and even involvement with it. These Christians have not turned away out of any deeply held convictions in support of the regime, but because they are worried by the militarisation and radicalisation of the revolution, and by the fact that after three years the opposition has still not shown itself to be a credible alternative to the regime. German and European policymakers should continue working towards a political solution and avoid supporting any particular religious or ethnic groups at the expense of others, because apart from those in areas where foreign Jihadists operate, Christians in Syria are no more at risk than other Syrians. (SWP Comments)